Cognition, social cognition and functional disability in early-stage schizophrenia: A study from southern India. (July 2018) - Kurtz, Matthew M.; Gopal, Subhashini; John, Sujit; Thara, R.
Highlights: Cognition and functional disability was studied in early schizophrenia in India. The magnitude and range of cognitive deficits was identical to Western samples. The magnitude of social cognitive deficits was more modest than Western samples. Negative symptoms, but not cognitive skills, were linked to functional disability. Abstract: In high-income countries a wealth of studies has revealed cognitive and social cognitive deficits in schizophrenia and a close relationship of these deficits to psychosocial functioning. Studies examining these illness features in middle and low-income countries are rare, particularly in early-stage samples. Sixty adult participants within 5 years of diagnosis with schizophrenia and 53 matched, healthy control were assessed with the MATRICS Consensus Cognitive Battery and the PEAT emotion identification task at study entry, and the WHODAS functioning scale one year later. Deficits on cognitive instruments ranged from d = 0.64–1.04 and were consistent with those reported in Western samples. Negative symptoms were linked to function longitudinally. Deficits in social cognitive skills and longitudinal links between cognition and functioning were not evident. These findings suggest a highly consistent magnitude of neurocognitive deficits in people with schizophrenia across widely varying cultures, but with limited evidence of social cognitive skill deficits using Western-based instruments. There was little evidence of a relationship between cognition and psychosocial disability in people with early-stage schizophrenia in this sample.